THE PHENOMENON OF ANTONYMY AND SYNONYMY IN IDIOMS IN ENGLISH AND UZBEK (European Journal of Interdisciplinary Research and Development, 2026)
This article investigates the phenomena of synonymy and antonymy in idiomatic expressions in English and Uzbek languages from a comparative perspective. Idioms, as stable and figurative language units, demonstrate semantic relations similar to lexical units, including synonymy and antonymy. The study analyzes how synonymous and antonymous idioms function in both languages, highlighting their structural, semantic, and cultural peculiarities. The research shows that while both languages share universal semantic patterns, their idiomatic expressions are strongly influenced by national and cultural contexts.